2017
DOI: 10.1002/ece3.3085
|View full text |Cite
|
Sign up to set email alerts
|

Temperature, energy metabolism, and adaptive divergence in two oyster subspecies

Abstract: Comparisons of related species that have diverse spatial distributions provide an efficient way to investigate adaptive evolution in face of increasing global warming. The oyster subjected to high environmental selections is a model species as sessile marine invertebrate. This study aimed to detect the adaptive divergence of energy metabolism in two oyster subspecies from the genus Crassostrea—C. gigas gigas and C. gigas angulata—which are broadly distributed along the northern and southern coasts of China, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 59 publications
8
48
0
Order By: Relevance
“…Studies found support for this hypothesis by showing that plastic responses of non-adapted individuals diminished differences to native populations (Lohman, Stutz, & Bolnick, 2017; Mäkinen, Papakostas, Vøllestad, Leder, & Primmer, 2016). Adaptive plasticity can also be indicated when plastic and evolutionary responses are in the same direction (Li, Li, Song, Wang, & Zhang, 2017), or when plasticity is higher in adapted populations (Hasan et al, 2017; McCairns & Bernatchez, 2009), suggesting that most plastic individuals were favored by selection. However, there are also examples for the reversed pattern suggesting that plasticity was maladaptive, at least on the long-term.…”
Section: Discussionmentioning
confidence: 99%
“…Studies found support for this hypothesis by showing that plastic responses of non-adapted individuals diminished differences to native populations (Lohman, Stutz, & Bolnick, 2017; Mäkinen, Papakostas, Vøllestad, Leder, & Primmer, 2016). Adaptive plasticity can also be indicated when plastic and evolutionary responses are in the same direction (Li, Li, Song, Wang, & Zhang, 2017), or when plasticity is higher in adapted populations (Hasan et al, 2017; McCairns & Bernatchez, 2009), suggesting that most plastic individuals were favored by selection. However, there are also examples for the reversed pattern suggesting that plasticity was maladaptive, at least on the long-term.…”
Section: Discussionmentioning
confidence: 99%
“…Temperature can considerably affect oxygen consumption, energy metabolism, mitochondrial efficiency and response to hypoxia-reoxygenation, and thus ATP-related functions (Abele, Heise, Pörtner, & Puntarulo, 2002;Chamberlin, 2004;Cherkasov, Biswas, Ridings, Ringwood, & Sokolova, 2006;Ivanina et al, 2012;Sokolova, 2004). As several loci (containing nonsynonymous mutations) located within genes known to have ATP-related functions were also associated with temperature, it is possible that adaptive divergence observed in the studied system could be linked with thermal adaptation and energetic metabolism, as revealed in other Crassostrea species (Li, Li, Song, Wang, & Zhang, 2017) and other molluscs (Sokolova & Pörtner, 2001;Tomanek & Zuzow, 2010).…”
Section: Highlights From Gene Ontologymentioning
confidence: 93%
“…Common garden experiments were conducted according to the methods of Li et al (2017) ( Supplementary Figure 2 ). Eggs from 30 uncontaminated mature female oysters of each population were mixed and divided into 30 replicates.…”
Section: Methodsmentioning
confidence: 99%